The Function of DNA Methylation Marks in Social Insects - Li-Byarlay, Hongmei (Frontiers in Ecology and Evolution, 2016)
The social arthropods are characterized by a caste-based division of labor that may be influenced by epigenetic effects. One of the most important and widely studied epigenetic mechanisms is DNA methylation. Advances in understanding of social insect genomes, including epigenetic marks, make it possible to assess the role of DNA methylation in social caste development and social behavior. In this mini review, I summarize and interpret recent findings regarding DNA methylation and discuss how DNA methylation might influence evolution of sociality. In particular, I focus on enzymes associated with DNA methylation, the functions of DNA methylation in caste determination, behavioral gene regulation, and the effects of DNA methylation on learning and memory. Finally, I highlight current challenges and predict future breakthroughs in the field of socioepigenomics.